"Perceived fit, " "understanding, " and "communication": Key factors underpinning stakeholder and partnership engagement with the Make Healthy Normal campaign. (11th November 2019) - Keane, Lewis; Kite, James; Grunseit, Anne; Vineburg, John; Tawil, Victor; Thomas, Margaret
Abstract: Issue addressed: Published evaluations of population‐level social marketing campaigns predominantly focus on impact and outcome evaluation. Evaluation of complementary locally implemented activities and programs, despite being common and important components of social marketing campaigns are rarely published. This study sought to examine the drivers of engagement of local implementers in the Make Healthy Normal campaign, implemented in New South Wales (NSW), Australia from 2015 to 2018, and to describe their engagement with the campaign as well as the scope and extent of complementary activities. Methods: We conducted 13 in‐depth semi‐structured qualitative interviews with health and nonhealth stakeholders from a range of urban, regional and rural settings across NSW. We analysed the interviews thematically, using an inductive and iterative approach. Results: We found stakeholder engagement (ie decision to buy into and commit resources) to the campaign was underpinned by two main drivers: "understanding", or how well they understood the campaign and their role in it, and "perceived fit", or how appropriate it was to their context. A third factor, "communication" functioned to enhance both understanding and perceived fit. Conclusion: Our results suggest that stakeholders would engage with the campaign more where they had a sound understanding of the campaign objectives and content, and an appreciation of how the campaign fits their strategic and procedural context. So What?: Campaign managers should incorporate clear, regular and efficient communication with local implementers and work with these groups early in the campaign development process. Organisers should also support and promote a "community of practice" approach to capitalise on the innovations of those promoting campaign messages at the community level.